FRI0547 Improved work participation in early rheumatoid arthritis in the netherlands 1995-2011. (23rd January 2014) - Britsemmer, K.; van der Weele, W.; van Schaardenburg, D.
Abstract : Background: During the past decades, major steps were made towards earlier diagnosis of rheumatoid arthritis (RA) and development of better therapies, leading to an improved prognosis of patients with early RA. Retaining work participation is increasingly accepted as an important outcome of RA treatment. Objectives: To study whether the work participation in early RA has changed in the Netherlands in the years 1995-2011. Methods: All incident patients with early RA according to the 2010 ACR/EULAR classification criteria and of working age (18-64 years), included from 1 January 1995 to 31 December 2009 in the Reade early arthritis cohort in Amsterdam, were selected. Patient cohorts were analysed in 5-year inclusion periods (1995-1999, 2000-2004, 2005-2009), corresponding to initial DMARD monotherapy, initial DMARD combination therapy and addition of biologics in case of non-response, respectively. The mean hours of paid work per week in the three subcohorts were analysed over time and compared to age and sex matched controls (data from the entire Dutch population [Statline database: www.cbs.nl ]) Results: The three subcohorts consisted of 138 (1995-1999), 206 (2000-2004) and 208 (2005-2009) patients at baseline. Five year follow-up data were available for 85, 122, and 62 patients, respectively. No significant differences in baseline age and DAS28 were found. Patients included in 1995-1999 had longer disease duration than patients included in the other sub-cohorts (median 5 months vs 4 and 3 months, respectively [p<0.001]). The percentage with paid work was 49% (1995-1999), 52% (2000-2004) and 60% (2005-2009) at baseline in RA patients compared to 61%, 64% and 66% in the general population (p<0.05, except for 2005-2009). After 5 years follow-up the percentages with paid work in early RA were 45%, 55% and 68%, respectively. Figure 1 shows the mean hours of paid work of early RA patients over 5 year follow-up compared to the mean hours of age and sex matched controls from the entire Dutch population. Image/graph: Conclusions: Work participation of early RA patients at their first visit was less than in the general population, but this difference declined in subsequent subcohorts. In working early RA patients, the mean hours of paid work were also lower than in the general population. Work participation rates and number of paid hours per week declined during follow-up in the patients included between 1995-1999, but remained at least stable in patients included in the later periods. A limitation is that no data were available on the timing of the presumed decline in work participation in the period before the diagnosis of RA. Although these data do not allow explanatory analysis, it is probable that the improved work participation after diagnosis is closely related to the earlier recognition and intensified treatment of early RA. Disclosure of Interest: None Declared